Morfologia pós-craniana de um novo espécime de Lestodon armatus Gervais, 1855 (Xenarthra, Mylodontidae) do quaternário do sul do Brasil - Peixoto, Dilson Vargas (2019)
During the Cenozoic of South America, the terrestrial sloths (Folivora) had wide adaptive irradiation that culminated in a great diversity of forms during the Pleistocene. Except for some arboreal species, most sloths were extinguished at the end of this period. Among the clades included in Pilosa, Mylodontidae was one of the most representative, showing a large number of species. The largest species of this clade was Lestodon armatus, whose distribution occupied a large portion of the continent. In this work, a new and well-preserved specimen (UFSM 11535) assigned to L. armatus is reported. The specimen was found in a new fossiliferous locality designated Arroio do Lestodon in the Seival Valley, Caçapava do Sul, Rio Grande do Sul, Brazil. UFSM 11535 includes vertebrae, ribs, teeth, and an articulated hindlimb that include almost all bones. A detailed description of these post-cranial bones was provided as well as a comparison with other specimens. The taxonomic assignation of UFSM 11535 to L. armatus is based on the presence of the following characters: I) separation of the ectal and sustentacular facets in the astragalus; II) the function of the ectocuneiform as metatarsal II by the fusion of the two bones; III) odontoid process of the astragalus in the form of a pulley with about 90º in relation to the discoid facet; IV) separation by a crest of the astragali facets in the tibia, and V) the medial condyle of the femur larger than the lateral condyle. Among the contributions to the knowledge on the variation of post-cranial morphology, the fusion between fibula and tibia and the presence of two sesamoids in the metatarsal III was recorded for the first time in L. armatus. As future perspectives, more comprehensive analyzes of the post-cranial morphology of Mylodontidae and other sloths are necessary to verify the presence of individual anatomical variations, as well as to test the phylogenetic relevance of the characters present in this region of the skeleton.